2,2'-diphenyl-3,3'-diindolylmethane: a potent compound induces apoptosis in breast cancer cells by inhibiting EGFR pathway. - Arijit Bhowmik (Public Library of Science (PLoS), 2013)
Despite recent advances in medicine, 30-40% of patients with breast cancer show recurrence underscoring the need for improved effective therapy. In this study, by in vitro screening we have selected a novel synthetic indole derivative 2,2'-diphenyl-3,3'-diindolylmethane (DPDIM) as a potential anti- breast cancer agent. DPDIM induces apoptosis both in vitro in breast cancer cells MCF7, MDA-MB 231 and MDA-MB 468 and in vivo in 7,12-dimethylbenz[α]anthracene (DMBA) induced Sprague-Dawley (SD) rat mammary tumor. Our in vitro studies show that DPDIM exerts apoptotic effect by negatively regulating the activity of EGFR and its downstream molecules like STAT3, AKT and ERK1/2 which are involved in the proliferation and survival of these cancer cells. In silico predictions also suggest that DPDIM may bind to EGFR at its ATP binding site. DPDIM furthermore inhibits EGF induced increased cell viability. We have also shown decreased expression of pro-survival factor Bcl-XL as well as increase in the level of pro-apoptotic proteins like Bax, Bad, Bim in DPDIM treated cells in vitro and in vivo. Our results further indicate that the DPDIM induced apoptosis is mediated through mitochondrial apoptotic pathway involving the caspase-cascade. To the best of our knowledge this is the first report of DPDIM for its anticancer activity. Altogether this report suggests that DPDIM could be an effective therapeutic agent for breast cancer.